6(x-9)=6

Simple and best practice solution for 6(x-9)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-9)=6 equation:


Simplifying
6(x + -9) = 6

Reorder the terms:
6(-9 + x) = 6
(-9 * 6 + x * 6) = 6
(-54 + 6x) = 6

Solving
-54 + 6x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + 6x = 6 + 54

Combine like terms: -54 + 54 = 0
0 + 6x = 6 + 54
6x = 6 + 54

Combine like terms: 6 + 54 = 60
6x = 60

Divide each side by '6'.
x = 10

Simplifying
x = 10

See similar equations:

| (3x-y)/(2x-Y)=1 | | (6x-3)+(9-7x)= | | 40-5(2x+10)=1 | | (3x-y)/(2x-y) | | 0.15t+2.50=6 | | 12.34+.08x=13.09-.11x | | -3+4k=5 | | 9m+32=6-4 | | 41+17.25x=24+21.50x | | -2x+3-5x-1=4x+5+x-1 | | 6(x+2)-(2x-3)= | | 3x^2+9xy+6y^2=0 | | 0=-16+t | | (4y-9)+40+5y=180 | | -y+7=15 | | 6(x-30)-5(x+35)=45-4(x-15) | | w-0.5=16 | | (x-3i)(x+3i)(x-(1+2i))(x-(1-2i))(x-6)=0 | | 15+47(922)= | | 9(-7+180)= | | 5(x+2)-4(x+1)=1 | | 0.7p+4.6=6.3-0.2p | | 5(-x+2)-4(x+1)=1 | | (60*10+3*10)+(60*G+3*G)= | | gx=4x^2-7 | | 8n=(4n+2)+20 | | x^-1/2-1/2x^-3/2 | | 4(d-6)+1=-11 | | 9x+3x+12= | | solve-5(2x-11)=(2x-3)-11 | | 300-16t^2=0 | | 3n-2+2(2n+1)=6n+7 |

Equations solver categories